Beef cattle mineral nutrition in the Brazilian Pantanal. VI. Micronutrients survey on the Aquidauana subregion. - Pott, Edison B.; Filho, Josê A. Comastri; Almeida, Irajá L. de; Brum, Paulo A. R. de; Pott, Arnildo (Pesquisa Agropecuaria Brasileira, 2014)
Samples of soil, forages and liver of lactating zebu cows were collected in November 1982, May and August 1983, and analysed for Fe, Mn, Cu and Zn. Soil and plants were sampled in five landscape units: forest, savanna, high and low Elyonurus grassland and open wet grassland. In soil of the landscapes mean levels of Fe varied from 29 to 112 ppm; Mn, from 15 to 66 ppm: Cu, from 0.4 to 3.1 ppm: and Zn, from 0.3 to 1.2 ppm. In forages (landscape means), Fe varied from 79 to 448 ppm; Mn, from 50 to 382 ppm; Cu, from 3.5 to 6.7 ppm; and Zn from 5 to 16 ppm. Liver presented, per season, mean levels of 477 to 558 ppm Fe; 25 to 35 ppm Mn; 228 to 284 ppm Cu; and 117 to 130 ppm Zn. There was no evidence of Fe, Mn, Cu or Zn deficiencies in animal tissue, but the low forage Zn levels and high levels of Fe in forages and liver allow to recommend Zn supplementation for beef cattle in the Aquidauana subregion.